Reducing heat losses from aging district heating pipes by using cured-in-place pipe liners. (15th June 2023) - Jing, Mengke; Zhang, Shujie; Fu, Lisong; Cao, Guoquan; Wang, Rui
Abstract: Low heat losses from district heating (DH) networks significant for efficient energy utilization and carbon emission reduction. However, the additional heat loss due to the aging of DH pipes is a serious challenge. Usually, it needs to be solved by pipe refurbishment. The novelty of this paper is that a new strategy was proposed: using cured-in-place pipe (CIPP) liners. This strategy can realize pipe maintenance without pipe refurbishment and large excavations. It has advantages in economic and social cost. After that, a new CIPP liner with an enhanced insulation function was designed to support this strategy. The obtained CIPP liner exhibited a variety of advantages, including low thermal conductivity, high mechanical properties, low water absorption and high thermal stability. Finally, a numerical simulation verified the effectiveness of the liner. The effect of using CIPP liners was affected by the liner parameters and working conditions. Based on a set of parameters, the liner reduced the heat loss of the aged pipe by 55.4%. This work provides a new perspective for the maintenance of DH pipes and contributes to the energy conservation of DH networks. Highlights: A new strategy was proposed to reduce heat losses of aging district heating pipes. Using CIPP liners can replace pipe refurbishment and avoid large excavation. A new CIPP liner with an enhanced insulation function was designed. CIPP Liners can reduce heat loss by 55.4% based on a simulation. Liner parameters and working conditions affect the effect of CIPP liners.